Leveraging faith-leaders to prevent violence against women and girls: A qualitative study of evangelical faith-leaders' perceptions in Woliso, Ethiopia. - Wosene Berhanu; Elisa Gobbo; Addise Amado Dube; Nesanet Megersa; Yoska Amenu; Mengistu Demeke; Adamu Addisse; Sibylle Herzig Van Wees (PLOS Global Public Health)
Background Violence against women and girls (VAWG) affects 1 in 3 women globally. Religion can be both a driver and a potential solution for VAWG. Evidence suggests that faith-leaders can create positive change around VAWG and improve ideas of gender equality, but it is critical to have a context-specific understanding of existing awareness. In Ethiopia, Evangelical faith-leaders' perceptions of VAWG have not been studied. Aim To increase understanding of Evangelical faith-leaders' perceptions of gender equality and VAWG and their views on how they can address VAWG, in Woliso, Ethiopia. Methods A qualitative study design drawing on 14 semi-structured interviews and observational data from workshops with Evangelical faith-leaders that explored their views on gender equality and VAWG. An inductive reflexive thematic analysis approach was used. Results The data analysis generated 4 themes, 8 sub-themes, and 22 categories. The themes include: (1) differing perceptions of VAWG as a problem in the community; (2) navigating between social and religious norms as explanations of VAWG; (3) differing interpretations of biblical scripture; and (4) navigating who has a role in countering gender inequality and VAWG. Many faith-leaders condemned forms of VAWG and expressed hopes for equality, but some failed to grasp all elements of VAWG and utilized religious reasoning to justify VAWG. The majority of faith-leaders expressed an interest in increasing awareness and held hopes for improved gender equality. Conclusion Faith-leaders hold different understandings of what constitutes VAWG. Faith-leaders' hopes for equality and their willingness to address VAWG indicates the potential of faith-leaders as important actors in VAWG prevention efforts. Yet, trainings and support are critical.